GRB14, GPD1, and GDF8 as potential network collaborators in weight loss-induced improvements in insulin action in human skeletal muscle - Park, Jung-Jun; Berggren, Jason R; Hulver, Matthew W; Houmard, Joseph A; Hoffman, Eric P (Physiological genomics, 2006)
1 Research Center for Genetic Medicine, Childrens National Medical Center, Washington, District of Columbia 2 Department of Exercise and Sports Science, East Carolina University, Greenville, North Carolina 3 Pennington Biomedical Research Center, Louisiana State University System, Baton Rouge, Louisiana Obesity is associated with insulin resistance in skeletal muscle; accordingly, weight loss dramatically improves insulin action. We sought to identify molecular remodeling of muscle commensurate with weight loss that could explain improvements in insulin action. Muscle from morbidly obese women was studied before and after gastric bypass surgery. Gastric bypass surgery significantly reduced body mass by 45% and improved insulin action. We then assessed mRNA profiles using a stringent statistical analysis (statistical concordance with three probe set algorithms), with validation in a cross-sectional study of lean ( n = 8) vs. morbidly obese ( n = 8) muscle. Growth factor receptor-bound protein 14 (GRB14), glycerol-3-phosphate dehydrogenase 1 (GPD1), and growth differentiation factor 8 (GDF8; myostatin) significantly decreased 2.4-, 2.2-, and 2.4-fold, respectively, after weight loss (gastric bypass). Increased expression of these transcripts was associated with increased obesity in the cross-sectional group (lean vs. morbidly obese muscle). Each transcript was validated by real-time quantitative RT-PCR assays in both study groups. Using Ingenuity Pathway Analysis, we show that all three transcripts are involved in the same regulatory network including AKT1, IGF1, TNF, PPARG, and INS. These results suggest that GRB14, GPD1, and GDF8 are weight loss-responsive genes in skeletal muscle and that the observed transcriptional modulation of these would be expected to improve insulin signaling, decrease triglyceride synthesis, and increase muscle mass, respectively, with weight loss. Thus our data provide a possible regulatory pathway involved in the development of insulin resistance in the morbidly obese state, and improvement of insulin resistance with weight loss. obesity; gastric bypass; mRNA profiling; growth factor receptor-bound protein 14; glycerol-3-phosphate dehydrogenase 1; growth differentiation factor 8